2009
DOI: 10.1016/j.molcel.2009.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Mislocalized Activation of Oncogenic RTKs Switches Downstream Signaling Outcomes

Abstract: Inappropriate activation of oncogenic kinases at intracellular locations is frequently observed in human cancers, but its effects on global signaling are incompletely understood. Here, we show that the oncogenic mutant of Flt3 (Flt3-ITD), when localized at the endoplasmic reticulum (ER), aberrantly activates STAT5 and upregulates its targets, Pim-1/2, but fails to activate PI3K and MAPK signaling. Conversely, membrane targeting of Flt3-ITD strongly activates the MAPK and PI3K pathways, with diminished phosphor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
287
2
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 284 publications
(311 citation statements)
references
References 59 publications
20
287
2
2
Order By: Relevance
“…We also observed a higher frequency of LT-HSC in KLI chimeras (Supplementary Figure 4F). However, there is evidence that Flt3 ITD/ þ mice have lower surface expression of the FLT3 receptor (Jacobsen, personal communication) probably due to entrapment of the FLT3 ITD in the endoplasmic reticulum 25,26 and therefore identification of LT-and ST-HSC using FLT3 may be problematic. Consequently, we decided to rely on expression of CD150 and CD48 (Figures 3a and b) to identify LT-HSC (LSKCD150 þ CD48 À ) and MPP (CD150 À CD48 þ ).…”
Section: Resultsmentioning
confidence: 99%
“…We also observed a higher frequency of LT-HSC in KLI chimeras (Supplementary Figure 4F). However, there is evidence that Flt3 ITD/ þ mice have lower surface expression of the FLT3 receptor (Jacobsen, personal communication) probably due to entrapment of the FLT3 ITD in the endoplasmic reticulum 25,26 and therefore identification of LT-and ST-HSC using FLT3 may be problematic. Consequently, we decided to rely on expression of CD150 and CD48 (Figures 3a and b) to identify LT-HSC (LSKCD150 þ CD48 À ) and MPP (CD150 À CD48 þ ).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it has been reported that the oncogenic mutant of fms-like tyrosine kinase-internal tandem duplication aberrantly activates STAT5 when localized at ER, but fails to activate MAPK and AKT signaling. 17 Thus, this raises the possibility that involvement of the STAT3 pathway in ALK del2-3 -expressing cells resembles the fms-like tyrosine kinase-internal tandem duplication mutant. 17 Immunofluorescence staining and the endoglycosidase H sensitivity assay revealed that ALK del2-3 is mainly located at ER and aberrantly activates the STAT3 pathway from ER.…”
Section: Discussionmentioning
confidence: 98%
“…17 Thus, this raises the possibility that involvement of the STAT3 pathway in ALK del2-3 -expressing cells resembles the fms-like tyrosine kinase-internal tandem duplication mutant. 17 Immunofluorescence staining and the endoglycosidase H sensitivity assay revealed that ALK del2-3 is mainly located at ER and aberrantly activates the STAT3 pathway from ER. Taken together, our results suggest that intracellular activation of ALK del2-3 switches downstream signaling to the ALK pathway.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…We therefore looked downstream from FLT3 to investigate whether signaling differences occurred during coculture on stroma. Of particular interest was STAT5, whose phosphorylation and subsequent activation is a hallmark of the oncogenic FLT3-ITD pathway (29,30). In MV4-11 cells, SU5614 inhibited phosphorylation of STAT5 in suspension and when cocultured with EL08-1D2 ( Fig.…”
Section: Flt3-itd-specific Downstream Signaling Is Uncoupled From Fltmentioning
confidence: 99%